Intralesional collagenase in the treatment of Peyronie's disease. (April 2014) - Honig, Stanton C.
The objective of intralesional pharmacotherapy in the treatment of Peyronie's disease is to deliver large doses of pharmacologic agents that can have a local effect on wound remodeling, with minimal side effects. Guidelines for the treatment of peyronie's disease published in the Journal of Sexual Medicine and the European Association of Urology offer no grade A evidence of efficacy with multiple agents such as steroids, verapamil and interferon. Intralesional collagenase is the first drug to be approved by the United States Food and Drug Administration for the treatment of Peyronie's disease. This is based on grade A evidence. The purpose of this update is to review the literature and current data on intralesional collagenase in the treatment of Peyronie's disease.